ผลของไคโทซานต่อประสิทธิภาพการกำจัดหมึกโทนเนอร์ด้วยวิธีการลอยฟองอากาศ - ธนพล ว่องวาณิช (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
The objective of this research was to investigate the effects of chitosan on flotation deinking efficiency of toner ink. Two factors studied were studied. The first factor was types of chitosan with three different molecular weights i.e. 1st chitosan with molecular weight of 32,000 Dalton, 2nd chitosan with molecular weight of 6,500 Dalton, and 3rd chitosan with molecular weight of 21,000 Dalton. The second factor was the dosage of chitosan which was 0.1% and 1.0% based on oven dried (O.D.) pulp weight. The experimental results indicated that molecular weight of chitosan had no statistically significant effect on optical and physical properties of handsheets prepared after flotation (P-value was higher than 0.05). However, the dosage of chitosan had a statistically significant effect on brightness, opacity, effective residual ink concentration (ERIC) and tear index (P-value was lower than 0.05) while it had no statistically significant effect on tensile index, burst index, freeness and apparent density. Higher dosage of chitosan resulted in lower brightness, higher opacity and higher ERIC possibly because too much chitosan reduced flotation deinking efficiency due to too large ink particles agglomerated by chitosan. Also, it might be because chitosan might react with pulp fibers more than ink particles due to the positive charge of chitosan and negative charge of pulp fiber. Thus, the chance of chitosan to collect ink particles might be decreased and more ink particles were left in the pulp. Higher dosage of chitosan also led to higher tear index since chitosan itself was a strength agent for paper.